The mediating effect of self-control on parenting and delinquency: a gendered approach with a multinational sample - Muftić, Lisa R. (International journal of offender therapy and comparative criminology, 2018)
This study aims to clarify the relationships between parenting techniques, low self-control, and juvenile delinquency in Gottfredson and Hirschi’s general theory of crime while controlling for alternative explanations of delinquency. We relied on a sample of 35,511 adolescent students from 31 countries from the International Self-Report Delinquency 2 Study. Results indicate that parenting exhibits a direct effect on adolescents’ violence perpetration and property offending, and that while self-control weakens the strength of this relationship, it fails to fully mediate it. Males reported lower levels of self-control, exposure to poorer parenting techniques, and higher rates of violence perpetration and property offending. The relationship between parenting, self-control, and juvenile delinquency was similar for females and males. These results provide evidence that parenting has important implications for adolescents’ involvement in delinquency above and beyond its influence on their level of self-control.